L'insertion socio-professionnelle transition majeure de l'existence - Fournier, Geneviève; Bujold, Charles; Drolet, Jean-Louis; Marcoux, Yves; Monette, Marcel; Riverin-Simard, Danielle; Spain, Armelle (Canadian Journal of Counselling and Psychotherapy, 1992)
In this article, five theoretical models of integration into the labor market are at first presented. Each of these views this integration as a major life transition. Seven research projects, bearing on this topic, are then examined in terms of their goals and their relationships to some of the five models. The practical implications of these projects for psychological education and career counselling are also outlined.